2016
DOI: 10.1016/j.midw.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with post-traumatic stress symptoms following childbirth in Turkey

Abstract: maternity care services in Turkey need to recognise the potential impact of birth experiences on women's mental health and adaptation after birth. The importance of self-efficacy in pregnancy suggests antenatal education or support may protect women against developing post partum PTS, but this needs to be examined further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 44 publications
5
13
0
Order By: Relevance
“…23,24 In this study, continuous urinary catheterization during childbirth was associated with high CityBiTS scores. Notably, a strikingly similar association was found in another study, 25 Gynaecologists 26 has not cited clear supporting evidence, it recommends intermittent catheterization during the first stage of birth and its complete discontinuation during the second stage.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…23,24 In this study, continuous urinary catheterization during childbirth was associated with high CityBiTS scores. Notably, a strikingly similar association was found in another study, 25 Gynaecologists 26 has not cited clear supporting evidence, it recommends intermittent catheterization during the first stage of birth and its complete discontinuation during the second stage.…”
Section: Discussionsupporting
confidence: 70%
“…4,7,19 In this study, higher CityBiTS scores were reported by (a) women whose privacy had not been respected during labor, (b) women who were confronted with the negative attitudes of health care personnel, and (c) women who did not have the support of primary midwives during the birthing process. According to the literature, PP-PTSD is more common among women who do not feel sufficiently supported during the birthing process, 19,22,25,30 feel despondent, lack help, and have to cope with the negative attitudes that they are confronted with. 3,6,14 Therefore, we believe that the uninterrupted management of a normal delivery by a midwife will help us to significantly reduce the risk of PP-PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is reasonable to speculate that higher prevalence rates of PTSD might result from sample differences as well as poor conditions of state hospitals and differing health care practices in Turkey, specifically the high rate of obstetric interventions (Gokce Isbir et al, 2016) and the authoritarian attitudes of midwives or health professionals towards women during birth (Sercekus and Okumus, 2009). However, there is no epidemiologic study of risk factors for perinatal PTSD in Turkey.…”
Section: Ptsdmentioning
confidence: 99%
“…In a limited number of studies on perinatal trauma in our country, it is observed that classical PTSD scales such as Posttraumatic Diagnostic Scale and Impact of Event Scale are used to assess PTSD symptoms related to childbirth (39)(40)(41)(42)(43)(44). While studies support that the Posttraumatic Diagnostic Scale is an effective screening criterion for the evaluation of PTSD associated with childbirth in postpartum women, it also suggests that the scale was developed according to DSM-IV diagnostic criteria was a limitation (39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…While studies support that the Posttraumatic Diagnostic Scale is an effective screening criterion for the evaluation of PTSD associated with childbirth in postpartum women, it also suggests that the scale was developed according to DSM-IV diagnostic criteria was a limitation (39)(40)(41)(42). The Impact of Event Scale was found to be used in two studies to examine the risk factors associated with the postpartum post-traumatic stress symptoms in our country and to examine the effects of prenatal education on fear of childbirth, self-efficacy and perinatal PTSD symptoms (43,44). According to the DSM-IV, the Impact of Event Scale used in the literature to measure perinatal trauma, measures only three clusters among the PTSD symptoms and can be associated with underestimation of PTSD dimension associated with childbirth (45,46).…”
Section: Introductionmentioning
confidence: 99%